Primary Hyperaldosteronism As A Risk Factor For Recurrent Nephrolithiasis - Ekamol Tantisattamo; Thomas B. Francis (The Korean Society of Nephrology, 2012)
Primary hyperaldosteronism typically presents as hypertension, hypokalemia, and metabolic alkalosis. Several previous reports note an association between primary hyperaldosteronism and nephrolithiasis with secondary hyperparathyroidism. We report a case of a previously normotensive, normocalcemic, normokalemic young man with initial CT imaging of nephrolithiasis showing no adrenal abnormalities. Three years later, he presented with severe hypertension, hypokalemia, and an adrenal adenoma with incidental findings of recurrent nephrolithiasis. Literature review of hyperaldosteronism complicating nephrolithiasis and possible etiologic mechanisms are reviewed. A 25 year-old man with a history of ureteral calculi 3 years ago presented with gastroenteritis for over 24 hours. Initial evaluation included a BP of 194/140 mmHg, potassium of 2.2 mmol/l, bicarbonate of 40 mmol/l, and ionized calcium of 0.95 mmol/l. All electrolytes 3 years prior were normal. Plasma aldosterone concentration to plasma renin activity ratio was 21.1 with aldosterone of 4 ng/dl and renin of 0.19 ng/ ml/ hr. CT scan showed a new 3 cm left adrenal mass not seen on prior CT with multiple new left renal stones. Follow up aldosterone after correction of hypokalemia, spironolactone, and amiloride was 104 ng/dl. Laparoscopic adrenalectomy pathologically confirmed an adrenal adenoma. Postoperative labs showed relative hypoaldosteronemia albeit with persisting but much improved hypertension. Hyperaldosteronism can cause hypercalciuria, phosphaturia, and hypocitraturia, all of which are risk factors for nephrolithiasis. Additionally, hyperaldosteronism and deoxycorticosterone mediated hypertension have been associated with hypocalcemia and secondary hyperparathyroidism. Our case augments earlier literature suggesting increased risk for nephrolithiasis in patients with hyperaldosteronism and suggests that hyperaldosteronism should be considered as a risk factor for patient with nephrolithiasis. It remains unclear if both primary and secondary hyperaldosteronism increase the relative risk for nephrolithiasis and the role of aldosterone receptor antagonist therapy for recurrent nephrolithiasis associated with hyperaldosteronism.